THE EFFECT OF ENGLISH SONGS BY USING JOOX APPLICATION ON STUDENTS' PRONUNCIATION - Dina Irma Yanti; Ayu Widiana Putri (Journal MELT (Medium for English Language Teaching), 2022)
This research aimed to determine the effect of English songs by using JOOX Application on students' English pronunciation in the Eighth Grade of SMP Swasta Harvard Martubung. This research used a quantitative approach with experimental random sampling. The population of this research was Eighth Grade students of SMP Swasta Harvard Martubung. The research groups were divided into an experimental group and a control group. Each group consisted of 30 students. Pre-test was given to the group at the beginning of the research phase. Then the treatment was given by using on the JOOX Application. The application was only given to the experimental group. The results showed that the JOOX Application had a significant effect on students' pronunciation. It could be seen from the average pre-test scores of both classes, the mean scores of pre-test in control group was 63,5 and the post-test was 76,7. While the average scores of the pre-test for the experimental group was 67,3 and the post-test was 82,7. It could also be seen from the t-test at the post-test value of 0,00 ≤ 0,05 which meant Null Hypothesis (Ho) was rejected and Alternative Hypothesis (Ha) was accepted. It showed that the JOOX Application had a significant positive effect on students' pronunciation. It meant that most of the students had positive responses after learning by using JOOX Application. So, it could be concluded that there is a significant effect between English songs and JOOX Application on students' pronunciation in the Eighth Grade of SMP Swasta Harvard Martubung.